A novel modification to boron-doped diamond electrode for enhanced, selective detection of dopamine in human serum. (January 2021) - Li, Haichao; Zhou, Kechao; Cao, Jun; Wei, Qiuping; Lin, Cheng-Te; Pei, Sharel E.; Ma, Li; Hu, Naixiu; Guo, Yaohua; Deng, Zejun; Yu, Zhiming; Zeng, Sichao; et al.
Abstract: In this work, we proposed a novel modification technique to immobilize nanoparticles by the nanopores on a boron-doped diamond surface, preventing the aggregation of nanoparticles physically and improving the stability of nanoparticles layer by the anchoring effect. All the exposed surfaces of a bare boron-doped diamond were etched into nanoporous form and larger electrochemically active surface area was obtained on the porous boron-doped diamond electrode. The carbon black nanoparticles modified porous boron-doped diamond electrode showed good selectivity to separate the oxidation potential of three molecules, but led to an extra increase in the peak current of dopamine (DA). The carbon black/Nafion modified porous diamond electrode effectively suppress the oxidation current of ascorbic acid (AA), enhancing the sensitivity of DA. The dual layer treatment enables a wide linear range, 0.1–100 μM and a low limit of detection, 54 nM for DA detection, which is almost unaffected by the excess AA and uric acid (UA). At last, real sample tests of the carbon black/Nafion modified porous diamond electrode was validated by applying to the detection of DA in human serum and dopamine hydrochloride injection, which were found to be promising at our preliminary experiments. Additionally, the fabricated carbon black/Nafion modified porous diamond electrode also demonstrated good stability and long-term functionality. Graphical abstract: Image 1 Highlights: A novel modification on porous boron-doped diamond electrode for determination of dopamine was developed. The elimination of the interference was realized and a low detection limit of 54 nM for DA was obtained. Reproducibility of the CB-Nafion/p-BDD electrode in real sample and excess interferents was validated. Excellent stability and long-term functionality of the CB-Nafion/p-BDD electrode were confirmed.